Adjuvant chemotherapy for undifferentiated embryonal sarcoma of the liver in adults: a case report and literature review - Xiong, Miaogang; Li, Zheng; Xiang, Yang; Yang, Gang; Xiong, Yongfu (Frontiers in Oncology, 2026)
Undifferentiated embryonal sarcoma of the liver (UESL) is a rare, highly aggressive malignant tumor that occurs predominantly in children and is exceedingly uncommon in adults. Its clinical presentation and auxiliary examinations lack specificity, making preoperative diagnosis challenging and the misdiagnosis rate high. This article reports a 33-year-old female adult with UESL who presented with right upper quadrant pain. MRI revealed a large mass in the right hepatic lobe. The patient underwent laparoscopic right hemihepatectomy and was diagnosed postoperatively. She subsequently received doxorubicin-based adjuvant chemotherapy. The disease recurred one year after surgery. Despite further surgical intervention and comprehensive treatment, the patient died 24 months postoperatively. This case suggests that while R0 resection combined with anthracycline-based adjuvant chemotherapy can prolong progression-free survival, adult UESL still carries a high risk of early recurrence and has a poor prognosis. After recurrence, the disease often progresses explosively and is resistant to multiple treatment modalities. By presenting the diagnosis and treatment experience and lessons from failure in this case, this study provides valuable insights for the clinical management of this rare disease.